The anti-hyperlipidemia effect of Yinlan capsule via regulation of PXR activity - Zhao Chen; Dongmei Li; Xi-Yuan Li; Guanlin Xiao; Xiaoli Bi; Weitao Chen; Zhiqi Shi; Xiaohui Zeng; Dongmei Sun; Li-Zhong Cao (Elsevier, 2021)
Background: Yinlan capsule is a complex TCM formulation that is prescribed for the treatment and prevention of hyperlipidemia. Our previous study indicated that one of the key targets of Yinlan is the Pregnane X Receptor (PXR). Purpose: To verify that PXR is the main active target for Yinlan's anti-hyperlipidemia effect, and to discover the agonists and antagonists with both suitable content and pharmacokinetic profile accordingly. Methods: an UHPLC-TOF-MS method was first applied to screen components in Yinlan capsule, peaks found in the ion current chromatogram were identified by the database (AB Sciex Analyst Software 1.6), and those with obvious responses were set as candidates; cytobiological experiment was carried out in the subsequent step, using HepG2 cell incubated with midazolam and monomer of the candidate compounds, yield of 1'-hydroxy- midazolam was used as an index to evaluate the PXR-CYP3A4 regulation activity of each component; a UHPLC-MS method was used for determination of the candidates showed obvious changes in 1'-hydroxy- midazolam yield, and compounds had suitable content in Yinlan capsule were validated for their PXR regulatory activities by QT-PCR; then components with both good PXR/CYP3A4 regulatory activity and suitable content underwent pharmacokinetic research to evaluate their in-body movements, compounds with acceptable pharmacokinetic parameters were finally chosen as quality marker of Yinlan's anti-hyperlipidemia effect via regulation of PXR activity. Comparisons of results in each step of evaluation were carried out using SPSS software, and the compounds with obvious difference (p<0.05, with model group or control) were marked as active ones. Results: The agonists (components in Yinlan that up-regulate the PXR activity) inhibit inflammatory reactions and promote the synthesis of bile and fatty acids, while the antagonists (components in Yinlan that down-regulate the PXR activity) accelerate energy metabolism and the decomposition of bile and fatty acids. In other words, the desired efficacy of Yinlan can be achieved when the activity of the antagonists surpasses the activity of the agonists. As it was indicated by content determination and pharmacokinetic research, the antagonists with adequate content and metabolomic profile to take effect showed greater efficacy over agonists. Conclusion: The anti-hyperlipidemic effect of Yinlan consequently results from suppressing PXR expression, promoting bile acid excretion, and fatty acid decomposition, and such activity results from the fact that the antagonist surpasses the agonist. It is suggested that both sides should be taken into consideration when investigating the therapeutic mechanism of Yinlan and the related active components.